P1445 DORv and window: a case of an uncorrected double outlet right ventricle with d-transposition of great arteries with concomitant aortopulmonary window in a 31-year-old female. (17th January 2020) - Enero, R; Obillos, S; Yao, P; Dizon, E; Choa, V; Go, L; Cheng, A; Carreon, A
Abstract: Funding Acknowledgements: none Double outlet right ventricle (DORV) is a rare type of ventriculo-arterial connection occurring in about 1-3% of congenital heart defects. Moreover, transposition of the great arteries, wherein the aorta is anterior and to the right of the pulmonary artery (D-TGA), accounts for only 26% of cases of DORV. An aortopulmonary window, on the other hand, represents approximately only 0.2% of all congenital cardiac lesions. A case of DORV with D-TGA and pulmonary stenosis with a concomitant aortopulmonary window has never been reported, particularly in an adult in the third decade of life and without any history of surgical repair. We present the case of a 31-year-old female who had sought consult for left-sided weakness. On physical examination, a grade IV/VI systolic murmur was heard at the left anterior chest and cyanosis of the digits of the upper and lower extremities were noted. Transthoracic echocardiogram revealed a non-restrictive ventricular septal defect (VSD) and segmental approach showed atrial and visceral situs solitus, levocardia, and atrioventricular concordance. However, there was ventriculoarterial discordance with fusiform aneurysmal dilatation of the aorta, which was noted to be at the right of and anterior to the pulmonary artery. Both great vessels arose from the right ventricle. Other echocardiographic findings included dilated right atrium, dilated and hypertrophied right ventricle with volume and pressure overload, global left ventricular hypokinesia with mild systolic dysfunction, and moderate to severe aortic regurgitation. The above complex congenital anomalies were confirmed via transesophageal echocardiogram and cardiac magnetic resonance imaging (MRI). Furthermore, pulmonary valve stenosis and aortopulmonary window, that was 3.5 centimeters in length located at the level of the proximal ascending aorta and main pulmonary artery, were seen on the MRI. Various cardiac imaging modalities aided in cinching the diagnosis for this very rare complex congenital case in an adult reaching the third decade of life. Palliative care was deemed best for this patient due to the severity of her cardiac condition.